Nitrogen/protein and one-step moisture and ash examination in foodstuffs: Validation case analysis using automated combustion and thermogravimetry determination under ISO/IEC 17025 guidelines - Cortés Herrera, Carolina (2021)
Method validation within food science is a not only paramount to assess method certainty and ensure the quality of the results, but a pennant in analytical chemistry. Proximate analysis is an indispensable requirement for food characterization. To improve proximate analysis, automated protein and thermogravimetric methods were validated according to international guidelines (including ISO 17025) and acceptance criteria of results based on certified reference materials and participation within international recognized proficiency schemes. Common food groups (e.g., meat, dairy, and grain products) were included and at the end of validation, we obtained three rugged and accurate methods with adequate z scores (−2 ≥ x ≤ 2) and recoveries (92–105%). During optimization, variables such as gas flows, subsample masses, and temperatures were varied and specific conditions (those that rendered the best results) were selected for each food group. For each validated method, a comparison (technical and economic) among the data obtained and the data extracted for its traditional counterpart were included: assays validated demonstrate to be more cost-effective labor-wise (ca. 9 and 16-fold) than their traditional alternatives. Specifically for combustion assay regression analysis (y = 0.9361x, y = 1.1001x, and y = 0.9739x, for meat, dairy and grain products, respectively) were performed to assess the factor, if any, which must be applied to the results to effectively match those obtained for Kjeldahl method. Finally, in the case of protein, samples can be analyzed under 5 min with no residue and a subsample mass below 400 mg. Moisture and ash analysis can be performed simultaneously using the same subsample. Data herein will also help harmonize and advance food analysis toward more efficient greener methods for proximate analysis.